Teacher Discipline and Loyalty as Drivers of Educational Quality in Islamic Schools: A Thematic Literature Review - Sari, Ice Rosina; Dermawan, Oki (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
Educational quality in Islamic schools is profoundly shaped by teacher professionalism, where discipline and loyalty serve as critical human resource drivers. Despite their theoretical linkage, empirical gaps persist regarding how these constructs interact to sustain instructional excellence. This study employs a qualitative thematic systematic literature review to synthesize peer-reviewed publications (2015–2024) examining teacher discipline, loyalty, and educational quality in Islamic contexts. Thematic synthesis reveals that discipline functions as a structural prerequisite for organizational stability, while loyalty operates as a psychological and professional commitment that sustains instructional continuity. The analysis demonstrates a synergistic relationship: internalized discipline fosters role clarity and procedural consistency, which, when mediated by fair leadership and value alignment, cultivates productive loyalty. This loyalty subsequently drives teacher retention, collaborative innovation, and student learning outcomes. The review underscores that disciplinary mechanisms rooted solely in administrative compliance are insufficient; sustainable educational quality requires integrating internalized professionalism, participatory governance, and Islamic ethical values into school management. These findings offer theoretical clarification on the discipline, loyalty, quality nexus and provide actionable insights for administrators designing policies that balance accountability, professional autonomy, and institutional commitment.